Crystallization of tRNA(Leu)-Synthetase from Baker's Yeast - Chirikjian, Jack G. (1972)
tRNA(Leu)-Synthetase from baker's yeast has been crystallized from ammonium sulfate solution. The crystals are of orthorhombic symmetry, falling into space group [unk] or [unk] with a = 75.5 Å, b = 110.7 Å, and c = 124.0 Å. This unit cell contains four molecules of the native (dimeric) enzyme, with eight asymmetric units, each corresponding to the enzyme subunit. Diffraction patterns obtained for the three major projections contain reflections to spacings of less than 3.5 Å, indicating that this crystal form is amenable to structure analysis to atomic resolution.